The spectrum of HIV-related kidney disease in South Africa - Dave, Nicola (Department of Medicine, 2025)
The spectrum of HIV-related kidney disease in South Africa Associate Professor Nicola Wearne Background: HIV is associated with a spectrum of kidney diseases, including HIV-associated nephropathy (HIVAN), opportunistic infections, including tuberculosis (TB), and adverse effects of drugs and immune activation/viral replication. This thesis explores the evolving landscape of HIV-related kidney disease in a setting where antiretroviral therapy (ART) has been progressively rolled out to all. Methods: This PhD comprises four studies: 1. A longitudinal study describing the relationship between HIV immune-virological status, ART usage, and kidney pathology. 2. A study of corticosteroids for the treatment of patients with HIVAN. 3. A descriptive analysis of kidney disease in the setting of HIV/TB coinfection. 4. A descriptive analysis of kidney pathology in biopsies from HIV-positive donors transplanted into HIV-positive recipients. Results: 1. Among 671 participants, an increase in ART usage was associated with a reduction in the proportion of biopsies showing HIVAN. In contrast, an increase in tubulointerstitial disease was associated with exposure to tenofovir disoproxil containing ART and likely TB. 2. We included 38 ART-naïve individuals with HIVAN, 21 of whom were randomly assigned to receive six months of prednisone. While adjunctive prednisone was associated with slightly more significant improvements in eGFR, mortality was increased in this group. 3. A high prevalence of acute and chronic kidney disease (CKD) in African people with HIV/TB was observed across three cohorts. TB affected the kidneys in 60% at post-mortem, and 8% had severe CKD with multiple aetiologies, including HIVAN, identified on kidney biopsy. 8 4. Based on 179 allograft biopsies from 50 recipients, we report a high cumulative incidence of rejection episodes, with 36% showing T-cell-mediated rejection or antibody-mediated rejection (ABMR). Non-rejection findings included fibrosis, pyelonephritis, and calcineurin toxicity. Features of HIVAN were identified in nine patients. ABMR significantly impacted kidney function and contributed to graft failure over 14 years. Conclusion: The studies document a shift in kidney pathologies among people with HIV in Cape Town, which was temporarily associated with the progressive rollout of tenofovir based ART. Corticosteroids cannot be recommended to improve kidney outcomes in patients with HIVAN. Kidney disease is a significant complication of HIV/TB. While HIV+ to HIV+ kidney transplantation is feasible, high rates of allograft rejection and infection suggest a need for carefully balanced immunosuppression.